Low-cost infrared thermography in aid of photovoltaic panels degradation research - Miguel Alberto Dávila-Sacoto; Luis Hernández-Callejo; Víctor Alonso-Gómez; Sara Gallardo-Saavedra; Luis Gerardo González-Morales (Revista Facultad de Ingeniería Universidad de Antioquia, 2020)
The analysis of PV solar panels deterioration allows researchers to know the health status of a panel in order to determine the overall functioning of a PV solar farm. A part of this analysis is performed by thermography, generally using professional and expensive equipment. This article presents a validation for the use of low-cost thermal imaging cameras, reviewing the relative error that can be obtained through scattering, contour analysis and three-dimensional meshes. The procedure is validated by analysis of I-V/P-V curves and a temperature sensor matrix, reaching errors less than 10% with cameras with less than 500USD.